Embeddedness of Moral and Culture Institutions with Embroidery Entrepreunership in Tasikmalaya - Jamilah, Joharotul; Dharmawan, Arya Hadi; K. Panjaitan,, Nurmala; S. Damanhuri, Didin (Sodality: Jurnal Sosiologi Pedesaan, 2016)
ABSTRACTIn the Era of Global Economy, in general the business world is controlled by the formal economic ethics. This means that the businesses with modern economic system dominates the behaviours of enterpreuneurs in his economic acts. Production relation that is constructed between the enterpreuners and the employers is rational formal relationship, such as the employment contract should be clear above “black and white”, and the SOP (Standard Operational Procedure) which has been determined from beginning or formal legal nature. However, there is still found the businessman with moral economic ethics as the basis of their behaviours may persist, including the businessman of embroidery industry in Tasikmalaya.This research is aimed to reveal the business strategy that is undertaken by the embroidery enterpreuners in order to survive in the modern economy which is based on capitalist economic ethics with formal rational, and how the moral values and formal underlying the relation of production between the businessman and the workers.The methode used in this research is case study, with 12 embroidery enterpreuners, according to the criteria of Legilation No. 20 Yr. 2008 about UMKM, in Tasikmalaya. The data collecting uses deep interview and observation, while the technique of data analysis is used descriptive qualitative analysis. The result of the study is there is an embeddedness of Islamic and Sundanese values in the economic acts of the embroidery enterpreuners in Tasikmalaya with difference of embeddedness level. i.e: (1) Strong embeddedness on the Islamic values and weak Sundanese ethics traditions, call as Islamic-Sundanese Entrepreneurs (2) Strong embeddedness on the Sundanese tradition and weak Islamic Ethics, call as Sunda-Islamic Entrepreneurs, and (3) Strong embeddedness on the modern economic ethics but weak on the Islamic and Sundanese ethics, call as Capitalist Entrepreneurs.Keywords: formal rational, moral ethics economy, Islamic-Sundanese Entrepreneurs, Sunda-Islamic Entrepreneurs, capitalist entrepreneursABSTRAKPada era ekonomi global, dunia bisnis pada umumnya dikendalikan dengan etika ekonomi formal. Hal ini berarti bisnis dengan sistem ekonomi modern mendominasi perilaku wirausahawan dalam tindakan ekonominya. Hubungan produksi yang terbangun antara pengusaha dengan pekerja bersifat rasional formal, seperti dengan adanya kontrak kerja yang harus jelas di atas ‘hitam putih’, dan SOP yang sudah ditentukan dari awal atau bersifat legal formal. Tetapi masih ditemukan pelaku bisnis dengan etika ekonomi moral sebagai dasar perilakunya dapat bertahan, diantaranya pengusaha industri bordir di Tasikmalaya. Penelitian ini bertujuan untuk mengungkap strategi bisnis yang dilakukan pengusaha bordir sehingga dapat tetap survive dalam ekonomi modern yang berlandaskan pada etika ekonomi kapitalis dengan rasional formal, serta sejauhmana nilai-nilai moral dan formal melandasi hubungan produksi antara pengusaha dengan pekerjanya berdasarkan tipologi pengusaha. Metode yang digunakan adalah studi kasus, pada 16 pengusaha bordir, sesuai kriteria UU no 20 tahun 2008 tentang UMKM di Tasikmalaya. Teknik pengumpulan data melalui deep interview dan observasi sedangkan teknik analisis data melalui analisis deskriptif kualitatif. Hasil yang didapatkan adalah adanya keterlekatan nilai Islam dan Sunda dalam tindakan ekonomi para pengusaha bordir di Tasikmalaya yang berbeda-beda derajat kelekatannya yaitu (1) keterlakatan kuat pada nilai Islam dan lemahetika budaya Sunda, disebut sebagai tipe Pengusaha Islami-Sundanis, (2) keterlakatan kuat pada nilai budaya Sunda dan lemah pada nilai Islam, adalah tipe Pengusaha Sunda-Islami, dan (3) terlekat kuat pada etika ekonomi modern dan lemah pada etika Islam dan Sunda, sebagai tipe Pengusaha KapitalisKata kunci : rasional formal, etika moral ekonomi, Pengusaha Islami-Sundanis, Pengusaha Sunda-Islami, pengusaha kapitalis